Educational Media Dental Colouring Book as an Innovation in Dental Health Education for Young Children - Fahima Arnas Syahilla; Sunomo Hadi; Sri Hidayati (Jurnal teknologi Kesehatan Borneo, 2025)
Oral health is an important aspect of comprehensive health and plays a significant role in children's growth. If disturbed, this condition can affect children's overall development and physical health, as well as reduce their quality of life. Dental caries in early childhood is a major concern because it reflects the effectiveness of dental health maintenance efforts. The problem in this study is the high percentage of dental caries in group B students at Al-Barokah Blega Bangkalan Kindergarten, which is likely caused by a lack of knowledge about dental caries, frequent consumption of cariogenic foods, minimal motivation, and irregular access to health services, especially dental health services, at Al-Barokah Blega Bangkalan Kindergarten. This study aims to determine the effectiveness of using the Dental Coloring Book media on changes in knowledge about dental caries among Group B students at Al Barokah Kindergarten in Blega sub-district, Bangkalan district. This research is a quantitative study with a pre-experimental design of the one-group pretest-posttest type, in which a pretest will be given before the intervention and a posttest after the intervention. This study involved 30 respondents from group B of Al-Barokah Blega Bangkalan kindergarten. Data analysis was carried out using the Wilcoxon test, with a result of sig = 0.000 < 0.05. This means that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted, indicating that counselling using the Dental Coloring Book medium was effective in improving the knowledge of Group B students at Al-Barokah Blega Bangkalan Kindergarten in 2025.